Signal modulation techniques in Non-orthogonal waveform for future wireless communication system - Siti Rosmaniza AR; Norulhusna Ahmad Ahmad; Sharifah Kamilah Syed Yusof (Institute of Advanced Engineering and Science, 2019)
In the future generation of the wireless communication system, the utilization of bandwidth needs to be managed efficiently. Due to that, research on enhancing the efficiency of the bandwidth has recently attracted numerous interests focusing more on the non-orthogonal waveform generation and detection. Even though non-orthogonal waveform is promising a higher efficiency, it introduces inter-carrier interference (ICI) at the transmitter due to the subcarrier overlapping. In this paper, the signaling technique for non-orthogonal waveform generation and detection is discussed. This paper also proposed the use of accumulator (ACC) to improve the system performance of the signal modulation in the non-orthogonal waveform for the next generation of the wireless communication system. The result is represented in an EXtrinsic Information Transfer (EXIT) chart to show the effects of adding ACC into the non-orthogonal system.